High‐efficiency transformation of archaea by direct PCR products with its application to directed evolution of a thermostable enzyme. Issue 2 (29th June 2020) - Song, Yunhong; Zhu, Zhiguang; Zhou, Wei; Zhang, Yi‐Heng P. Job
Summary: Hyperthermophilic archaea with unique biochemical and physiological characteristics are important organisms for fundamental research of life science and have great potential for biotechnological applications. However, low transformation efficiency of foreign DNA molecules impedes developments in genetic modification tools and industrial applications. In this study, we applied prolonged overlap extension PCR (POE‐PCR) to generate multimeric DNA molecules and then transformed them into two hyperthermophilic archaea, Thermococcus kodakarensis KOD1 and Pyrococcus yayanosii A1. This study was the first example to demonstrate the enhanced transformation efficiencies of POE‐PCR products by a factor of approximately 100 for T. kodakarensis KOD1 and 8 for P. yayanosii A1, respectively, relative to circular shuttle plasmids. Furthermore, directed evolution of a modestly thermophilic enzyme, Methanothermococcus okinawensis 3‐hydroxy‐3‐methylglutaryl coenzyme A reductase (HMGR), was conducted to obtain more stable ones due to high transformation efficiency of T. kodakarensis (i.e. 3 × 10 4 CFU per μg DNA). T. kodakarensis harbouring the most thermostable MoHMGR mutant can grow in the presence of a thermostable antibiotic simvastatin at 85°C and even higher temperatures. This high transformation efficiency technique could not only help develop more hyperthermophilic enzyme mutants via directed evolution but also simplify genetical modification of archaea, which could be novel hosts for industrial biotechnology. Abstract : We developed a very simple technology to transfer prolonged overlap extension PCR (POE‐PCR) products to two hyperthermophilic archaea with enhanced transformation efficiencies. Via it, we can evolve mesophilic enzymes to hyperthermophilic ones by directed evolution.